Increases in sexually transmitted infections and sexual risk behaviour without a concurrent increase in HIV incidence among men who have sex with men in San Francisco: a suggestion of HIV serosorting?. Issue 6 (6th December 2006) - Truong, H-H M; Kellogg, T; Klausner, J D; Katz, M H; Dilley, J; Knapper, K; Chen, S; Prabhu, R; Grant, R M; Louie, B; McFarland, W
Abstract : Background: Sexually transmitted infections (STI) and unprotected anal intercourse (UAI) have been increasing among men who have sex with men (MSM) in San Francisco. However, HIV incidence has stabilised. Objectives: To describe recent trends in sexual risk behaviour, STI, and HIV incidence among MSM in San Francisco and to assess whether increases in HIV serosorting (that is, selective unprotected sex with partners of the same HIV status) may contribute to preventing further expansion of the epidemic. Methods: The study applies an ecological approach and follows the principles of second generation HIV surveillance. Temporal trends in biological and behavioural measures among MSM were assessed using multiple pre-existing data sources: STI case reporting, prevention outreach programmatic data, and voluntary HIV counselling and testing data. Results: Reported STI cases among MSM rose from 1998 through 2004, although the rate of increase slowed between 2002 and 2004. Rectal gonorrhoea cases increased from 157 to 389 while early syphilis increased from nine to 492. UAI increased overall from 1998 to 2004 (p<0.001) in community based surveys; however, UAI with partners of unknown HIV serostatus decreased overall (p<0.001) among HIV negative MSM, and among HIV positive MSM it declined from 30.7% in 2001 to a low of 21.0% in 2004 (p<0.001). Any UAI, receptive UAI, and insertive UAI with a known HIV positive partner decreased overall from 1998 to 2004 (p<0.001) among MSM seeking anonymous HIV testing and at the STI clinic testing programme. HIV incidence using the serological testing algorithm for recent HIV seroconversion (STARHS) peaked in 1999 at 4.1% at the anonymous testing sites and 4.8% at the STI clinic voluntary testing programme, with rates levelling off through 2004. Conclusions: HIV incidence among MSM appears to have stabilised at a plateau following several years of resurgence. Increases in the selection of sexual partners of concordant HIV serostatus may be contributing to the stabilisation of the epidemic. However, current incidence rates of STI and HIV remain high. Moreover, a strategy of risk reduction by HIV serosorting can be severely limited by imperfect knowledge of one's own and one's partners' serostatus.